Coronavirus disease 2019 and preterm birth: A systematic review and meta analysis - Zhibek Oralkhan; Gulmira Zhurabekova; Ibrahim A Abdelazim; Aidana Pazylbek (National Scientific Medical Center, 2021)
Background: The COVID-19 pandemic is a challenge for the healthcare system in most countries and its association with adverse pregnancy outcomes, especially preterm birth is controversial. The present study aim to understand the relation between severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection of pregnancy and outcome of preterm birth. Methods: A search was performed in Cochrane Library, PubMed Scopus, E library and local databases up to 30 April, 2021. Searching strategy was used PICOS (Population, Intervention, Comparison and Outcomes, study design) framework. Study group included COVID-19 pregnant patients compared with healthy pregnant women. Main outcome was perform birth(<37 gestational week). The data were extracted from two authors and statistical analyses carried out using Review Manager (RevMan). Random-effects meta-analysis was conducted to calculate odds ratios (ORs) and weighted mean differences with 95% confidence intervals (CI). Results: Twenty six cohort studies involving 436695 pregnant participants were included in this study. Covid 19 was associated with significantly increased risk of preterm birth [OR =1.30 (1.20-1.39); p =0.02; I2 =41% ]. Conclusion: COVID-19 may be associated with increased risks of preterm birth, it is important to further understand the mechanism that explain the association and identify effective prevention methods to avoid Covid19 caused adverse pregnancy outcome.